Saúde sexual e reprodutiva : avaliação dos serviços de atenção primária nos municípios de Cuiabá e Várzea Grande - Mato Grosso - Vinhal, Criziene Melo (2018)
The attention to the reproductive health starts as a component of Brazilian public politics initially with demographic interest, used in the range of familiar planning without worrying with the quality of the practices of attention. In 2005, the Health Ministry incorporated in its guidelines of SUS the term sexual health, considering the right to the sexual and reproductive health, as a fundamental conquer of Human Rights, and its fulfillment is a way of promoting the life in society, being one of the priorities actions in primary attention of health. The National Politics of Basic Attention (hereby PNAB) characterizes the Primary Attention of Health in the politic being the first level of attention that comprehends the promotion and the health protection, the prevention of loss, the diagnosis, the treatment, the rehabilitation, the reduction of damage and the management of health, the development of evaluation of actions of this attention in the Public Health System becomes priority. The aim of the study is, therefore, to evaluate the organization of the actions of sexual and reproductive health in the Primary Attention to Health in the two biggest cities of the state of Mato Grosso. It is an evaluative research, with quantitative approach and transversal delineation, using as instrument the questionnaire QualiAB of the system of Monitoring and Evaluation of Quality of Basic Attention, developed and validated by the Department of Public Health of the Paulista State University, in partnership with the Department of Preventive Medicine of the University of São Paulo. The field of sexual and reproductive health in QualiAB is evaluated in three domains: promotion to sexual and reproductive health; prevention and assistance to infections sexually transmitted, aids, viral hepatitis and attention to reproductive health. The subjects of the research were professional of APS working as manager in 77 UBS of Cuiabá and 17 UBS of Várzea Grande, who participated with 84,0% of adherence of the 112 UBS existing in these cities of Cuiabá and Várzea Grande. The analysis of data showed that Cuiabá reached the best result in the actions of assistance, pointing that a dimension of management had a smaller performance of quality. Várzea Grande had worst results compared to Cuiabá. The actions of sexual and reproductive health with better performance is the prevention and the assistance to the loss of sexual transmission to IST/aids and viral hepatitis are the ones that had a better performance in both cities, with a satisfactory standard of quality. The attention to reproductive health is in an intermediary degree and the worse indicators are about promotion of Sexual and Reproductive Health, being the actions with an insufficient performance. The results indicate that the performances of the services of sexual and reproductive health in APS of Cuiabá and Várzea Grande are incipient.